WTO in crisis : exploring the dimensions of institutional inertia - Wilkinson, Rorden (2001)
Seeks to contribute to the post-Seattle analysis. Offers a different reading of the sources of the WTO's current inertia by placing Seattle within the context of the evolution of post-war international trade regulation. Argues that the roots of the WTO's inertia lie not with the Seattle Ministerial Meeting, or even with the post-Uruguay era, but with the creation of institutionalised trade regulation in the post-war period. Argues also, that the development of post-war trade regulation has been such that an institutional path dependency has emerged which has constrained the range of political possibilities deemed appropriate for moving beyond Seattle and taking the trade agenda forward.